Surgical management for localised penile cancer - Dimitropoulos, Konstantinos (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of various surgical treatments for localised penile cancer, including oncological efficacy, quality of life and functional impact. (FS: do we need to be more specific than this?) The comparisons of interest are:  one type of surgery versus another; ; surgical treatment versus non‐surgical treatment.